Detection of Rabies Virus Antigen in Dog Saliva Using a Latex Agglutination Test - Kasempimolporn, S. (American Society for Microbiology, 2000)
Dog bites are responsible for more than 90% of human rabies deaths in Asia. We developed a simple and inexpensive test based on latex agglutination (LA) for rabies virus antigen detection in dog saliva. Rabies virus antigen could be detected by agglutination on a glass slide using latex particles coated with gamma globulin. By evaluation of paired saliva-brain specimens from 238 dogs, the LA test using saliva was 99% specific and 95% sensitive compared to the fluorescent antibody test (FAT) on brain smears. The advantages of the LA test over the standard FAT are that it is comparatively simple and there is no need to kill the animal before examination.